Risk assessment and thromboprophylaxis for venous thromboembolism in the puerperium in a tertiary health facility in Nigeria - Abbey, Mkpe; Green, Kinikanwo I.; Iheagwam, Roseline; Akani, Chris (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Venous thromboembolism (VTE) is a leading cause of maternal morbidity and mortality in the puerperium. Unfortunately in Nigerian tertiary institutions, there is paucity of information about its risk factors, screening for it, and its prophylaxis. The aim of the study therefore was to review the VTE risk and thromboprophylaxis in the puerperium at the University of Port Harcourt Teaching Hospital (UPTH), Nigeria. Methods: A retrospective cross-sectional study carried out at the University of Port Harcourt Teaching Hospital (UPTH). The following data were extracted from the notes of 424 consecutive inpatients postnatal women who delivered from the 1st of January to the 30th of April 2020: history/demographic characteristics, risk factors for VTE using the RCOG Green top guideline No. 37a.of 2015 as a benchmark, thromboprophylaxis, diagnosis and treatment of VTE. Women with a VTE event in the preceding 4 months before pregnancy were excluded. Data was analysed using a statistical package for social science (SPSS) software, version 18. Results: Risk assessment for VTE and its prophylaxis in the puerperium were not routine practice at the UPTH. 420 (99.06%) out of the total 424 postpartum women that were assessed were at significant risk of developing VTE and therefore needed to be on thromboprophylaxis with low molecular weight heparin. Irrespective of the high prevalence of risk factors and the fact that 100 (23.58%) of the patients had symptoms and signs of VTE, no case of VTE was recorded in the study population. Paucity of information and lack of knowledge about the diseases may be responsible for that. Conclusions: 420 (99.06%) out of the total 424 puerperal women were at significant risk of developing VTE and therefore needed to be on thromboprophylaxis in the puerperium. It was therefore recommended that a national guideline on VTE in the puerperium be written, taking into consideration local disease topography, ethnic diversity and the level of economic development in Nigeria.